Factors Affecting the Frequency of K1 Visits for Pregnant Women in Maternal Health Programs - Mukti Rahajeng; Tut Rayani Aksohini Wijayanti; Sulistiyah Sulistiyah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
This study aims to identify the factors that influence the first antenatal visit (K1) among pregnant women. The study employed a descriptive design with a cross-sectional approach, utilizing a total sampling technique. A total of 49 respondents, all of whom made the K1 visit, were included in the study. The variables examined in this research included maternal age, parity, and gestational age at the time of the K1 visit. Secondary data obtained from medical records were used for analysis. The results revealed that the majority of pregnant women who made the K1 visit were in the non-risk age group (20–35 years), accounting for 84% of the respondents. Regarding parity, most participants were multiparous, making up 53% of the total sample. In terms of gestational age, 43% of respondents made their K1 visit during the first trimester of pregnancy (0–12 weeks). The study found that the first antenatal visit was predominantly conducted by pregnant women in the non-risk age group (20–35 years) and the multiparous group. Additionally, the K1 visits were most frequently made when the gestational age was in the first trimester, reflecting early engagement with antenatal care. These findings highlight the importance of maternal age, parity, and gestational age in influencing the timing of the first antenatal visit, which plays a critical role in ensuring early and adequate prenatal care for pregnant women. These insights can be used to improve strategies for encouraging timely K1 visits, particularly for pregnant women who may be at risk of delayed prenatal care.